Dispute settlement reports 2017. World Trade Organization. (Cambridge University Press, 2018)
The Dispute Settlement Reports are the WTO authorized and paginated reports in English. They are an essential addition to the library of all practicing and academic trade lawyers and needed by students worldwide taking courses in international economic or trade law. DSR 2017: Volume 7 reports on Indonesia - Importation of Horticultural Products, Animals and Animal Products (WT/DS477, WT/DS478).